Pemanfaatan Software Eprints dalam Penelusuran Kumpulan Karya Ilmiah di Perpustakaan Universitas Andalas - Pasrah, Nurhaden; Marlini, Marlini (Ilmu Informasi Perpustakaan dan Kearsipan, 2016)
In this papers discussed about utilization of Eprints Software in search collecting scientific work in library of Andalas University. The aims are for describe: (1)To know the utilization of Eprints Software to search collecting scientific work in library of Andalas University; (2)To know what are the problem in search utilization of Eprints Software to search collecting scientific work in library of Andalas University; (3)To know the effort to resolve the problem of utilization of Eprints Software to search collecting scientific work in library of Andalas University.The research methods used in this papers is descriptive. Data collected through observation and interview with librarian of Library Andalas University. Data analysis performed on librarian who use Eprints Software in technology and information. Library’s study use the book, journals, internet, and other literature which relate with Eprint Software.Based result of research, concluded the following things. Second, the problem of using Eprints Software: (1) Less socialization between library’s visitor and librarian; (2) It constrained for moving from CD ( Compact Disc) to Eprint Software, (3) There’s no sub-menu to search scientific works; (4) the scientific work which slided is not concistent and not accordance with established. Third, the effort of problem which have performed on using Eprints Software are; (1) Teach the library’s visitor to utilization eprints software with good and give the special training for librarian; (2) it order to reached needs information for library’s visitor, librarian should be establish cooperation (3) It’s to esier do searching, it will be better submenu added for search scientific work; (4) expected to librarian and information technology staff more carefully.Keywords: utilization; software; eprints